2016
DOI: 10.1055/s-0036-1593362
|View full text |Cite
|
Sign up to set email alerts
|

Comparing ε-Aminocaproic Acid and Tranexamic Acid in Reducing Postoperative Transfusions in Total Knee Arthroplasty

Abstract: Multiple studies have shown tranexamic acid (TXA) to reduce blood loss and transfusion rates in patients undergoing total knee arthroplasty (TKA). Accordingly, TXA has become a routine blood conservation agent for TKA. In contrast, ε-aminocaproic acid (EACA), a similar acting antifibrinolytic to TXA, has been less frequently used. This study evaluated whether EACA is as efficacious as TXA in reducing postoperative blood transfusion rates and compared the cost per surgery between agents. A multicenter retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 17 publications
0
37
0
Order By: Relevance
“…Three included studies reported the outcome of the transfusion units per patient [ 7 , 9 , 10 ]. The random model was employed according to a significant heterogeneity ( χ 2 = 26.32, df = 2, I 2 = 92%, P < 0.00001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three included studies reported the outcome of the transfusion units per patient [ 7 , 9 , 10 ]. The random model was employed according to a significant heterogeneity ( χ 2 = 26.32, df = 2, I 2 = 92%, P < 0.00001).…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of DVT had been reported in six studies [ 6 , 7 , 9 – 12 ]. The low significant heterogeneity was found, a fixed model was applied ( χ 2 = 1.17, df = 5, I 2 = 0%, P = 0.95).…”
Section: Resultsmentioning
confidence: 99%
“…30 Amicar has been noted to have similar efficacy and safety to TXA with the addition of being more cost-effective. 31 However, it has not been as widely studied as TXA, which has a 6-to 10-fold increased affinity for plasminogen. 11 Larger, head-to-head studies are needed to determine if there is a clear indication for the use of one over the other.…”
Section: Tranexamic Acidmentioning
confidence: 99%
“…ε-ACA is an inexpensive medication with a low risk profile (does not carry any risk of anaphylaxis), making it a viable substitute for the generally more expensive antifibrinolytic TXA. 13,16 Studies have already confirmed that topical and intravenous administration can reduce blood loss after knee and hip joint replacement surgery. 17,18 Previous studies have confirmed the use of intravenous TXA by comparing it to aminocaproic acid with similar results regarding total blood loss and transfusion index after TKA.…”
mentioning
confidence: 96%
“…Moreover, the optimal timing and dosage of oral TXA remain unclear, as well as in the case of epsilon-aminocaproic acid (ε-ACA) using empirically high doses in an attempt to replicate the clinical effects of TXA. 13 Each AMICAR (aminocaproic acid) tablet for oral administration contains 1,000 mg of aminocaproic acid and the following inactive ingredients: povidone, crospovidone, stearic acid, and magnesium stearate.…”
mentioning
confidence: 99%